Exploring Physics: Engaging Inquiry-Based Labs for SMAN 1 Muaro Jambi's Class X - Munthomimah, Ririn; Yamin, Martinis; Rusdi, Muhammad (Program Magister Teknologi Pendidikan Universitas Jambi, 2022)
This research is a research development which aims to meet the availability of of physic learning materials based inquiry laboratory activities that can improve the effectiveness and attractiveness of the teaching of physics in class X SMAN 1 Muaro Jambi. This research method to adapt the model ADDIE which consists of five main stages of the Analysis, Design, Development, Implementation, and Evaluation. The resulting product has been evaluated through a process of expert validation of learning materials, learning technologies expert validation, testing peers, individual testing, small group testin, and testing of large groups. Data was collected through questionnaires, interviews, and assessment of learning outcomes. From the results of questionnaires and interviews showed that the developed teaching materials physics has been well categorized and fit for use. From the assessment of learning outcomes in the cognitive, psychomotor, and affective successively obtained an average value of students 76, 80, and 80 were categorized as having good learning outcomes.